THE RELATIONSHIP BETWEEN CLIMATE VARIABILITY AND INFANT DIARRHEA IN A COASTAL AREA OF JAKARTA - Dharmayanti, Ika; Purwana, Rachmadhi; Tjandrarini, Dwi Hapsari; Soesilo, Tri Edhi Budhi (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
This study examines climatic patterns and the delayed relationship between climate factors and diarrheal cases in this age group. This ecological panel study uses secondary data on monthly diarrhea cases in Penjaringan Subdistrict, North Jakarta, Indonesia. Diarrhea cases obtained from the DKI Jakarta Provincial Health Office between 2013 and 2024 (144 months). Climate factors included temperature, rainfall, relative humidity, and El Niño–Southern Oscillation (ENSO) index. The analysis of climatic patterns was examined descriptively. Associations were analyzed using a negative binomial mixed-effects model with distributed lags to account for delayed effects and spatial heterogeneity. The results indicate that infant diarrhea cases varied significantly by season. An increase of 1°C in temperature at lag 1 increased the case rate by 35% (IRR = 1.35; p = 0.038). Rainfall at lags 0 and 1 showed a small but substantial positive relationship with diarrhea. Higher relative humidity was associated with a lower risk, while ENSO conditions were positively associated with diarrhea. The study found that local meteorological conditions and large-scale climate variability influence the incidence of infant diarrhea in coastal areas. The novelty of this study lies in integrating a distributed lag model with ENSO effects on vulnerable populations. These findings support the development of climate-sensitive monitoring and early warning systems, and strengthening water, sanitation, and hygiene interventions during periods of high climate risk may help reduce the burden of diarrheal disease among high-risk groups.